Tailored Lead-Free KNN/BFO Perovskite Ferroelectric Film Heterostructures for Enhanced Electrofunctional Properties via Interface-Modulated Bilayer Design - Zhang, Wei (Langmuir : the ACS journal of surfaces and colloids, 2024)
In this work, a bilayer lead-free perovskite ferroelectric structure was fabricated comprising a highly polar BiFeO3 (BFO) bottom layer and a less polar (K1-xNax)NbO3 (KNN) top layer. The BFO sublayer, deposited via radio frequency magnetron sputtering without postgrowth annealing, not only exhibited enhanced crystallinity but also promoted superior microstructural properties in the sol-gel derived KNN overlayer, thereby ensuring excellent intrinsic electrical properties. Compared to the poorly crystallized single-layer KNN films directly synthesized on LNO-buffered (100)-Si substrate, the KNN layer in the bilayer structure demonstrated a strong (100) texture, along with a dense, homogeneous, fine-grained morphology. The bilayer design effectively balances the limited polarization of single-layer KNN and the weak dielectric response of single-layer BFO. Furthermore, variations in BFO sublayer thickness reveal that the KNN/BFO stacking configuration and interface characteristics play a crucial role in tailoring the electrical properties, even surpassing the intrinsic contributions of the individual layers. The presence of the BFO layer enhanced the unsaturated polarization in the KNN film, with a more pronounced effect as the BFO thickness increased. The dielectric constant of the KNN/BFO bilayer consistently fell between those of the two single-layer structures and decreased with increasing BFO thickness, contrary to the trend observed in single-layer BFO. These results underscore the complex interactions among intrinsic properties, stacking configurations, and interface coupling in lead-free ferroelectric films, providing insights for future heterostructure design strategies